Bullying Victimization Among Peruvian Children: The Predictive Role of Parental Maltreatment - Benavides Abanto, Carlos Martin (Journal of interpersonal violence, 2021)
Bullying among schoolchildren is increasingly being recognized as a major problem. Although previous studies have examined parental maltreatment as a risk factor for bullying, the evidence on this topic remains limited in Latin America. The aim of this study was then to measure the prevalence of bullying victimization among a nationally representative sample of Peruvian children and to test the association between bullying victimization and parental maltreatment in Peru. This study used a pooled data set from the 2013 and 2015 Peru National Surveys on social relations. Participants were Peruvian children aged from 9 years to 11 years in the fourth, fifth, and sixth grade of primary in both public and private schools nationwide. The results indicated that almost one third of Peruvian children have experienced physical bullying and nearly half of them psychological bullying. However, only a small percentage reported experiencing bullying very frequently. Furthermore, it was found that parental maltreatment in any form—physical or psychological—was strongly and positively associated with physical and psychological bullying victimization. The results also showed that the probabilities of being physically or psychologically bullied were higher among children who experienced physical or psychological parental maltreatment than among children who have not experienced such violence. The probabilities of being bullied were even higher among children who experienced both types of parental maltreatment. Consistent with previous research, these findings suggest that the relationship that children establish with their parents will largely determine how they interact with their peers.